BMC Rheumatology BMC Series – open, inclusive and trusted.
BMC Rheumatology is an open access, peer-reviewed journal that considers pre-clinical, translational and clinical articles on all aspects of the prevention, treatment and management of rheumatological diseases, related systemic and inflammatory conditions and associated comorbidities, as well as epidemiology, education, pathophysiology, genetics, and drug development.   .